Kill the boer : government complicity in South Africa's brutal farm murders - Roets, Ernst (Pretoria : Kraal Uitgewers, 2018)
"Kill the Boer: Government complicity in South Africa's brutal farm murders by Ernst Roets, activist, attorney and deputy CEO of the civil rights organisation AfriForum, lays bare the brutal reality of farm attacks in South Africa. Among other things it investigates the level of complicity in the crisis by the South African government. The book reveals accounts of direct involvement of members of the ruling ANC, the South African government and the South African Police Service (SAPS) in the planning and execution of farm attacks. Roets also argues that the South African media is complicit as analyses of news reports strongly point towards biased reporting on the issue of farm attacks and farm murders. Kill the Boer outlines the reasons why farm attacks are unique and why it deserves to be regarded as a priority crime. Roets has been actively campaigning for the prioritising of farm attacks since 2012"--https://www.graffitibooks.co.za/af/360760/Boeke/Ernst-Roets-Kill-the-Boer
"Commissioned by AfriForum."
Includes bibliographical references (pages 385-389) and index
Keywords: Farmers -- South Africa -- Social conditions; Farmers -- Government policy -- South Africa; Agriculture and politics -- South Africa; Murder -- South Africa; Farmers -- Crimes against -- South Africa